1972
DOI: 10.1161/01.cir.46.5.989
|View full text |Cite
|
Sign up to set email alerts
|

Atresia of the Left Coronary Artery Ostium

Abstract: Symptoms and electrocardiographic changes of acute myocardial ischemia in a 10year-old boy resulted from congenital atresia of the ostium of the left coronary artery. At 14 years of age persistence of symptoms and a positive exercise test prompted surgical treatment by aortocoronary artery saphenous vein bypass graft. Two months postoperatively, the symptoms and the abnormal findings on exercise test had subsided and forward flow through the graft to the left coronary artery was demonstrated by contrast angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Gibson et al reported 2 cases.11) In one patient, a membrane-like structure partially covered the left sinus of Valsalva, almost isolating the ostium of the left coronary artery; the other patient had severe stenosis of the proximal left coronary artery and a congenital HLCA cusp. Mullins et al (1972) reported on a 10 year old boy with atresia of the LCA ostium12) who developed a fainting episode while sitting as a spectator at a school athletic event. He was successfully treated with aortocoronary bypass surgery (ACBG).…”
Section: Discussionmentioning
confidence: 99%
“…Gibson et al reported 2 cases.11) In one patient, a membrane-like structure partially covered the left sinus of Valsalva, almost isolating the ostium of the left coronary artery; the other patient had severe stenosis of the proximal left coronary artery and a congenital HLCA cusp. Mullins et al (1972) reported on a 10 year old boy with atresia of the LCA ostium12) who developed a fainting episode while sitting as a spectator at a school athletic event. He was successfully treated with aortocoronary bypass surgery (ACBG).…”
Section: Discussionmentioning
confidence: 99%
“…2 The surgical treatment for LMCA has not been established. Although coronary artery bypass was the procedure of choice in many cases reported previously, 1,2,8,9 long-term patency, especially when using the saphenous vein in pediatric patients, was questionable. Therefore, we selected reconstruction of the left main coronary artery.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Among the different surgical approaches, including various forms of coronary artery bypass (eg, using the saphenous vein or internal mammary artery), reconstruction is the current technique of choice. However, postoperative coronary artery stenosis is a major complication.…”
mentioning
confidence: 99%
“…Isolated atresia of the origin of the left coronary artery is a rare anomaly8' 10, 22 Mullins et al 8 suggested that failure of canalization of the proximal segment of the left coronary anlage was responsible for this lesion. Although case 2 had atresia of the proximal segment of the left coronary artery, the coexistent deformity of the left coronary artery cusp may suggest a localized teratogenic effect late in embryogenesis or in fetal life as a more likely explanation for this lesion.…”
Section: Casementioning
confidence: 99%